2016
DOI: 10.3892/ol.2016.5440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-23a on anoxia-induced phenotypic transformation of smooth muscle cells of rat pulmonary arteries and regulatory mechanism

Abstract: We investigated the possible implication of miR-23a in anoxia-induced phenotypic transformation of the pulmonary arterial smooth muscle and studied the mechanism of upregulation of miR-23a expression in anoxia. The collagenase digestion method was used for preparing rat primary pulmonary artery smooth muscle cell (PASMC) culture. SM-MHC, SM-α-actin, calponin-1 and SM22α protein expression levels were evaluated using western blot analysis after the ASMCs were subjected to anoxia treatment (3% O2). Transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…MiR-210-5p promotes epithelial–mesenchymal transformation, an important contributor to the development of HPH, by inhibiting the expression of PIK3R5 [ 33 ]. Yan et al reported that miR-23a is highly expressed in hypoxia-treated pulmonary artery smooth muscle cells (PASMCs) and plays an important role in hypoxia-induced phenotypic transformation of PASMCs [ 34 ]. In the past 5 years, miR-23a has been found to be a biomarker for idiopathic PH [ 35 ] and a possible therapeutic target for pulmonary arterial hypertension because it promotes cell proliferation and migration by targeting the BMPR2/Smad1 signal in hypoxia-induced PASMCs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-210-5p promotes epithelial–mesenchymal transformation, an important contributor to the development of HPH, by inhibiting the expression of PIK3R5 [ 33 ]. Yan et al reported that miR-23a is highly expressed in hypoxia-treated pulmonary artery smooth muscle cells (PASMCs) and plays an important role in hypoxia-induced phenotypic transformation of PASMCs [ 34 ]. In the past 5 years, miR-23a has been found to be a biomarker for idiopathic PH [ 35 ] and a possible therapeutic target for pulmonary arterial hypertension because it promotes cell proliferation and migration by targeting the BMPR2/Smad1 signal in hypoxia-induced PASMCs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which hypoxia leads to changes in miRNA expression can be mediated by hypoxia inducible factor-1- (HIF-1-) dependent and HIF-1-independent pathways. Although hypoxia reportedly induces PASMCs phenotypic switching, the expression levels of miR-23a [ 92 ], miR-9 [ 93 ], miR-214 [ 36 ], and miR-20a [ 94 ] are increased, while those of miR-449 [ 95 ], miR-206 [ 96 ], miR-124 [ 97 ], miR-30c [ 98 ], and miR-140 [ 99 ] are decreased.…”
Section: Mirnas Modulate Pasmcs Phenotypic Switchingmentioning
confidence: 99%
“…miR-23a: miR-23a is involved in the development of various cancers, promotes cardiac hypertrophy, and antagonizes muscle atrophy [ 102 , 103 ]. Yan et al showed that under hypoxic conditions the expression of miR-23a was upregulated in primary rat PASMCs through a mechanism involving HIF-1a [ 92 ]. In addition, the expression of contractile protein markers was significantly downregulated, suggesting that miR-23a regulates the dedifferentiation of PASMCs.…”
Section: Mirnas Modulate Pasmcs Phenotypic Switchingmentioning
confidence: 99%
See 1 more Smart Citation